KNOWLEDGE MANAGEMENT DAN PENGARUHNYA DALAM PENGAMBILAN KEPUTUSAN PADA BADAN PEMBENTUKAN PERATURAN DAERAH DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN TAKALAR - Muh. Said; Fatmawati Fatmawati; Lukman Hakim (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2020)
Changes in the environment experienced by organizations require organizations to make adjustments to answer all future challenges. The strength that must be possessed by the organization is to realize the concrete concept that becomes a tool to make changes. One of them is knowledge management, because knowledge management is an organizational activity that manages knowledge as an asset, wherein various strategies there is the right distribution of knowledge to the right people in a fast time until they interact with each other from various knowledge and apply it in daily work for performance improvement. Knowledge Management integration in the decision-making process can be interpreted as a structured and systematic process in acquiring, distributing, and utilizing knowledge to support the decision-making process. The position of knowledge management in decision making is between two poles of knowledge, namely tacit knowledge on the one hand and the utilization of explicit knowledge in decision making on the other. Explicit knowledge emphasizes the implicit role of knowledge management in influencing actors involved in decision making. Research design using quantitative methods. The instruments used in this study were questionnaires. The results showed that the implementation of Knowledge management has a positive effect on decision making in the Regional Development Agency of Takalar regency.